2022
DOI: 10.1155/2022/9675342
|View full text |Cite
|
Sign up to set email alerts
|

Research on Online Education Curriculum Resources Sharing Based on 5G and Internet of Things

Abstract: Information technology has brought great changes to China’s education. 5G technology provides a better guarantee for the sharing of curriculum resources, facing the extreme shortage of educational resources in China. The contradiction between limited educational resources and unlimited development needs of higher education has become increasingly prominent. How to effectively realize resource sharing among universities has become a problem that must be considered in the talent development of universities. In o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A good teaching ecosphere should be constructed in a way that makes acceptable use of the benefits offered by the development of technology and promotes the general development of individuals working in the education sector in the future [77]. The China education development has found that new technology development, namely information technology represented by 5G, has a beneficial impact on class instruction [78]. Similar to the evolution of online education, the growth of design education has been intricately intertwined with the history of technological advancement.…”
Section: Technological Advancementmentioning
confidence: 99%
“…A good teaching ecosphere should be constructed in a way that makes acceptable use of the benefits offered by the development of technology and promotes the general development of individuals working in the education sector in the future [77]. The China education development has found that new technology development, namely information technology represented by 5G, has a beneficial impact on class instruction [78]. Similar to the evolution of online education, the growth of design education has been intricately intertwined with the history of technological advancement.…”
Section: Technological Advancementmentioning
confidence: 99%
“…Additionally, tertiary education institutions are collaborating with communication companies in equipping graduates with technical expertise and entrepreneurial skills in 5G technology standards and use cases [78]. Thus, 5G could play a vital role in transforming education, including: 5G technology for AR and VR in education [79]; development of mobile applications that use VR for education [80]; sharing of online curriculum resources based on 5G and IoT [81]; and so forth. Indeed, some institutions like Obuda University in Hungary have already introduced 5G technology in their curriculum at both undergraduate and postgraduate levels [82].…”
Section: A Mobile Industry Goals For 5g Networkmentioning
confidence: 99%
“…The curriculum is developed by employing a conceptual analysis with an integrative approach relevant to elementary to higher education levels to build student and parent participation [42]. Schools need curriculum development and learning relevant to the online learning challenges, such as developing an integrative curriculum [43] and applying an online education curriculum involving the 5G Internet of Things [44]. New concepts of curriculum development and learning in the era of online learning, such as Virtual Mobility (VM) and Open Education (OE), can significantly facilitate learning effectiveness as they offer flexibility and conformity to the characteristics of modern global schools [45].…”
Section: Curriculum and Learning Aspectsmentioning
confidence: 99%